Appraisal of Face-to-Face Interaction in Open and Distance Learning System in Nigeria - Olakulehin, Felix Kayode; Ojo, Olagbenga David (West African Journal of Open and Flexible Learning, 2014)
A major challenge confronting open and distance learners is the problem of isolation, boredom and loneliness, as a result of the inability to constantly meet with their tutors and peers. To address this challenge, many distance leaching institutions in Nigeria have established the face-to-face system to complement the instructional materials issued to their learners. This paper reviews the practice of open and distance learning in Nigeria, with an analysis of the effectiveness of use of face-to-face system along with other teaching materials. In conclusion, the study attempted to present a mix of approaches to face-to-face interaction in open and distance learning, which can be regarded as sustainable considering the socio-economic realities in present day Nigeria and the need for open and distance learning to meet the demands for Education For All.
Keywords: Face to face